(untitled) (Progressive Agriculture, 2018)
The study was undertaken to investigate the effects of Spirulina platensis on body weight, blood glucose and lipid profile on alloxan induced diabetic rats. Fifteen Long Evans male rats at six weeks of age were used for the experiment. Diabetes was induced by intraperitoneal injection of alloxan@ 150 mg/kg and experiment was carried out for a period of 6 weeks. Rats were divided into three groups of 5 rats each. The groups were i)healthy control, ii) diabetic control with both receiving rats’ pellet as supplement, and iii) diabetic treated with oral administration of Spirulina platensis @ 400 mg/kg bwt. Results from the study showed that Spirulina platensis reduced blood glucose significantly (P<0.01) and increased body weight significantly (P<0.05) in contrast to diabetic control group after 6 weeks. Lipid profile analysis with Spirulina platensis @ 400 mg/kg showed that total cholesterol, plasma triglycerides, and LDL were lowered significantly compared to diabetic groups in contrast to HDL levels which were increased following the use of Spirulina platensis. Our findings showed that oral administration of Spirulina platensis could reduce the adverse effect of alloxan induced diabetes in rats. Based on this research it can be concluded that Spirulina platensis has antihyperglycemic and hypolipidimic effects in alloxan induced diabetic rats. Progressive Agriculture 29 (2): 139-146, 2018